8 - Workable Social Health Insurance Systems in Sub-Saharan Africa: Insights from Four Countries - Olatunji Olugbenga, Ebenezer (Africa Development, 2017)
One of the major barriers to access to healthcare in most sub-Saharan African countries is financial constraints. The need therefore arises for African states to put in place workable social health insurance schemes, as is the practice in most developed countries. This article assesses the peculiar characteristics of sub-Saharan African countries that may impact on their ability to build capacity and effectively govern social health insurance schemes for their populations in a sustainable manner. In doing so, it draws from the experiences of countries that have experimented with different approaches to health insurance with varied outcomes. While Ghana has recorded some success, Nigeria and Rwanda have been able to domesticate their policies within a legal framework, yet South Africa is still to detach itself completely from health structures of the apartheid era. In sum, implementation faces a myriad of challenges in these countries and a lot remains to be done. What are these challenges and what steps are being taken to address them? How can other African countries learn from their experiences? Using four African countries as case studies, this article seeks responses to these questions. Specifically, it argues that sub-Saharan African countries need to take account of their socio-cultural, economic and political environments in fashioning their own health insurance strategies that will be pragmatic, socially acceptable and economically sustainable so as to meet the present and future needs of their populations, rather than an unwholesome adoption of the Western model. In making broad recommendations for countries on account of common challenges and experiences, This article emphasizes the importance of transparency in resource governance, unassailable accountability and greater political will by African governments for the eventual workability of their health insurance schemes.